2008
DOI: 10.1517/14656566.9.12.2161
|View full text |Cite
|
Sign up to set email alerts
|

Sibutramine: current status as an anti-obesity drug and its future perspectives

Abstract: Background : Obesity has become a global epidemic with recent estimates of > 400 million obese adults. Despite this, there are few safe and effective pharmacological interventions for obesity. Sibutramine is a weight loss agent, for use as an adjuvant to a comprehensive program of calorie restriction, exercise and behavioral therapy. Objective : The goal of this article is to review the available literature of pharmacological interventions for obesity and specifically to ex amine data with sibutramine for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 149 publications
(148 reference statements)
0
11
0
Order By: Relevance
“…The pharmacological treatment of DIO rodents with anti-obesity agents, such as sibutramine and liraglutide, has been shown to have effects comparable to those reported in humans. Sibutramine reduces food intake, but there are conflicting data as to whether sibutramine has an effect on energy expenditure [67] . In DIO rats, sibutramine has also been shown to reduce body weight compared to placebo (9%) because of a reduction in food intake.…”
Section: Polygenic Modelsmentioning
confidence: 99%
“…The pharmacological treatment of DIO rodents with anti-obesity agents, such as sibutramine and liraglutide, has been shown to have effects comparable to those reported in humans. Sibutramine reduces food intake, but there are conflicting data as to whether sibutramine has an effect on energy expenditure [67] . In DIO rats, sibutramine has also been shown to reduce body weight compared to placebo (9%) because of a reduction in food intake.…”
Section: Polygenic Modelsmentioning
confidence: 99%
“…[25][26][27][28] Sibutramine is one of the few established and well-proven agents for obesity and may be considered effective in the management of patients requiring pharmacotherapy as part of the multi-modal approach to weight-loss. [29][30][31][32] Though this serotonin-norepinephrine reuptake inhibitor was originally evaluated for possible use as an antidepressant, its research development was redirected to evaluate it as an anorexiant. [33] The pharmacological mechanisms by which sibutramine exerts its weight loss effect are likely due to a combination of reduced appetite, feelings of satiety, and possibly the induction of thermogenesis.…”
mentioning
confidence: 99%
“…12,13 In the present paper we describe the mechanism of action of sibutramine and present the most important trials that evaluated the body weight-reduction potential of this agent. Furthermore, we comment on recent studies evaluating the effects of sibutramine on cardiometabolic risk factors and in specific pathological conditions related with obesity such as polycystic ovary syndrome, sleep apnea syndrome, left ventricular hypertrophy, binge eating disorder and in adolescent obesity.…”
Section: Dovepressmentioning
confidence: 99%
“…30 In addition, it should not be administered to patients receiving monoamine oxidase inhibitors, selective serotonin reuptake inhibitors, sumatriptan, dihydroergotamine, meperidine, methadone, pentazocine, fentanyl, lithium or tryptophan. 13,30 However, a Swedish study reported that 28% of the patients prescribed sibutramine had one or more contraindications to its use. 47 In the larger sibutramine studies, discontinuation rates at one and two years of treatment were 19%-49% and 42%, respectively.…”
Section: Safety Considerationsmentioning
confidence: 99%